PREPARATION AND CHARACTERIZATION OF NANOPARTICLES OF KLASON AND KRAFT LIGNIN FROM Eucalyptus grandis WOOD - Stygar Lopes, Marina; Nisgoski, Silvana; Elita Carneiro, Mayara; Gonzalez de Cademartori, Pedro Henrique; Ines Bolzon de Muniz, Graciela (Floresta, 2024)
This work aimed to prepare and characterize nanoparticles of lignin produced from sawdust (Klason lignin) and black liquor (Kraft lignin), materials considered to be industrial waste. The raw material of this study was Eucalyptus grandis chips. For Klason lignin, the procedures were carried out according to the TAPPI 222 and, for Kraft lignin, the chips were cooked to collect the black liquor, followed by acid precipitation. The nanolignins were obtained by the mechanical process through a mill using passes from 2, 8 and 13. The characterization of nanolignins was performed by scanning electron microscopy with elemental chemical analysis and transmission electron microscopy, granulometry analysis, thermogravimetric analysis and differential scanning calorimetry. Scanning electron microscopy and transmission electron microscopy showed irregular nanostructures of various shapes and spherical structures, the latter of which were more evident and frequent in Kraft nanolignin. The elemental chemical analysis showed that the washing process of the nanolignins was satisfactory, as only a small percentage of sulfur was detected in the samples. The granulometric measurement confirmed that the nanolignins had nanometric dimensions. Thermal analysis showed the nanolignins had three degradation bands, attributed to the drying of the samples and also to the degradation of hemicelluloses and lignin itself. Therefore, it was possible to confirm the obtainment of Klason and Kraft nanolignins through the use of the mill, and that an increasing number of passes produced a greater portion of particles with nanometric size.